Consumer Behavior in Islamic Perspectives: A Theoretical Review - Sari, Niken Permata; Artha, Bhenu; Bahri, Bahri; Sari, Utami Tunjung; Hadi, Antonius Satria; Aditya, Ascasaputra; Asri, Cahya Purnama; Dinka, Cynta Alya (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
Islamic consumer behavior is guided by Islamic values and principles, which emphasize meaningful consumption connected to well-being, responsibility, moderation, and resource conservation. This study aims to produce a theoretical synthesis of consumer behavior from an Islamic perspective. In order to accomplish the goals and objectives of the research, a theoretical literature survey is carried out, and a conceptual framework for further investigation is provided. The normative framework of Islamic consumer behavior is explicitly determined by Maqasid al-Shari'ah, which provides a clear hierarchy of needs (Dharuriyyat, Hajiyyat, Tahsiniyyat) to guide ethical income allocation, avoiding israf and tabzir.